A HIGH-PERFORMANCE FIR FILTER ARCHITECTURE FOR FIXED AND RECONFIGURABLE APPLICATIONS - Priyadarshini, E. Mary; Manimegalai, P.; Chellaganeshavalli, S. (Pakistan Journal of Biotechnology, 2017)
The efficient distributed arithmetic (DA)-based approaches for high-throughput reconfigurable implementation of finite impulse response (FIR) filters whose filter coefficients change during runtime. Conventionally, for reconfigurable DA-based implementation of FIR filter, the lookup tables (LUTs) are required to be implemented in RAM; and the RAM-based LUT is found to be costly for ASIC implementation. Therefore, a shared-LUT design is proposed to realize the DA computation. Instead of using separate registers to store the possible results of partial inner products for DA processing of different bit positions, registers are shared by the DA units for bit slices of different weightage.The Proposed presents high speed digital Finite Impulse Response (FIR) filter relying on Booth multiplier and Carry Select Adder (CSLA) Using Parallel Pipelining Architecture. Adder has three architectures such as basic CSLA using RCA (Ripple Carry Adder), CSLA using BEC (Binary to Excess-1 Converter) and CSLA using D-latch. In this paper we propose 4-tap FIR Filter architecture using 16-bit CSLA using D-latch and 8-bit Booth tree multiplier. These multipliers and adders are used for high speed operation of digital FIR filter.